Synthesis and Crystal Structure of Binuclear Ni(II) Complex Derived from 2-Nitrobenzoic Acid and Tetramethylethylenediamine - M. Qadir, Adnan (Asian Journal of Chemistry, 2013)
A nickel(II) complex of the formula [Ni2(nba)4(tmen)2(H2O)]·C2H5OH (1), where nba = 2-nitrobenzoate, tmen = tetramethylethylenediamine, has been synthesized and determined by single crystal X-ray diffraction method. The crystal belongs to monoclinic system, space group P121/c1 with cell dimensions of a = 11.3931 (4), b = 33.0702 (4), c = 13.5623 (4) Å, a = 90, b = 111.310 (4) and g = 90°. The two nickel atoms are connected by one bridging water molecule and two bidentate bridging carboxylate ligands. The octahedral environment around each nickel atom is completed by two nitrogen atoms from tetramethylethylenediamine and one oxygen atom from monodentate carboxylate.